IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DALAM MENERAPKAN SIKAP TOLERANSI DAN PERSAUDARAAN DI SMP NEGERI 4 LAMONGAN - Muhammad Abid Nasrullah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Nasrallah, Abid. 2023. Islamic Religious Education to Create an Attitude of Tolerance and Brotherhood at SMP Negeri 4 Lamongan. Thesis, Islamic Religious Education Program, Postgraduate, University of Kiai Abdullah Faqih Gresik. Advisor: Muhammad Rofiq, M.Pd., M.Si.In a society filled with religious, racial, ethnic, and social diversity including within Islam its elfconflicts often arise that can eventually develop into disputes or even competition between Islamic groups or between religious communities. One form of conflict that often occurs is misunderstanding. Differences in interpreting attitudes or actions between religious adherents, even within the internal environment of a religion, can trigger tension. Therefore, it is important for every individual from different racial, ethnic, and religious backgrounds to foster an attitude of tolerance and a spirit of brotherhood.This is also reflected in the context of SMP Negeri 4 Lamongan, where in the process of learning Islamic Religious Education and the formation of morals by teachers, the values ​​of tolerance and brotherhood are instilled through learning activities at school and through various other religious activities. Islamic Religious Education in this school has an important role in fostering an attitude of tolerance and a spirit of brotherhood, which is formulated through the following research questions: (1) How is the implementation of Islamic Religious Education in forming an attitude of tolerance and brotherhood in SMP Negeri 4 Lamongan? (2) What is the impact of implementing an attitude of tolerance and brotherhood in the implementation of Islamic Religious Education in SMP Negeri 4 Lamongan?The results of the study revealed that: 1) The implementation of Islamic Religious Education learning in forming attitudes of tolerance and brotherhood at SMP Negeri 4 Lamongan was carried out through: (a) Flag Ceremony; b) provide an understanding of science so that religious people do not hate each other; c) commemoration of Islamic holidays; d) Actions that strengthen tolerance and brotherhood; e) Is universal and does not discriminate against students. f) maintain respect and respect; 2) The impact of implementing education on the application of attitudes of tolerance and brotherhood at SMP Negeri 4 Lamongan includes:a) Creation of a pleasant and conducive learning atmosphere; b) School runs smoothly and tolerance is high. c) Develop an attitude of mutual respect, respect and accept differences; d) Realization of religious harmony in diversity.